2019
DOI: 10.1080/13621718.2019.1573010
|View full text |Cite
|
Sign up to set email alerts
|

Tool eccentricity in friction stir welding: a comprehensive review

Abstract: This paper reviews research on the effect of tool eccentricity in the friction stir welding process. A distinction between pin profile eccentricity and tool eccentricity is addressed, followed by an in-depth review of the research progress in both of the cases, including the mechanism behind the eccentric motion and how it influences the overall joint outcome. Suggestions are made regarding potential future works in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 103 publications
(154 reference statements)
1
13
0
1
Order By: Relevance
“…13a). In-plane forces oscillation is associated with the eccentricity of the process [36] introduced by the system, the tool, and the interaction with the material to be welded [37]. Hence, during its period, the tool is making two different movement associates with the rotation.…”
Section: Discussionmentioning
confidence: 99%
“…13a). In-plane forces oscillation is associated with the eccentricity of the process [36] introduced by the system, the tool, and the interaction with the material to be welded [37]. Hence, during its period, the tool is making two different movement associates with the rotation.…”
Section: Discussionmentioning
confidence: 99%
“…The former studies suggested that during FSW process, a large proportion of F x and F y is generated owing to the interaction between the probe and material, and more than 90% of F z is caused by the compression action from the shoulder on the workpiece [25]. The periodic oscillation of the welding forces is closely related to the eccentric motion of the tool, the tool probe profiles and the periodic variation of interfacial sticking and slipping during the welding process [20,26,27]. Generally, to the FSW process controlling tool plunging depth as constant, the stabilization of the welding forces and their waveforms indicates the heat generation, material flow and weld formation are essentially stable, which are beneficial to the quality of the weld [28].…”
Section: Welding Force Characteristicsmentioning
confidence: 99%
“…It is mainly because the heat generation and welding thermal cycle depend not only on the welding parameters [17], but also the interface frictional conditions, hot plastic deformation, heat transfer, etc., during the welding process [18,19]. It is worth noting that FSW is a mechanically metallurgical process, and the above key points may be highly responded by the variation of welding forces generated due to the interactions of the tool and the workpiece [20]. Thus, this offers the potential to predict the characteristics of M-A constituents and impact toughness of SZ with higher accuracy when considering the force features and further gives a guide for developing the strategy to modifying M-A constituents and improving the toughness of SZ in FSW joint.…”
Section: Introductionmentioning
confidence: 99%
“…摩擦攪拌接合および点接合用ツールの形状には,特にプ ローブの断面形状に注目した場合,円形型と非円形型に大 別することができる 1,2) .プローブの断面が非円形型の場合, プローブの先端や外周のエッジ部が切削工具における切れ 刃のような働きをすることが報告されている [3][4][5] .この中で, 摩擦攪拌点接合(以下,FSSW )において,接合材料を切り くず状にしながら排出し [6][7][8]…”
Section: 緒 言unclassified